Egg-laying site, fecundity and degree of sexual size dimorphism in frogs. (15th September 2020) - Silva, Nelson Rodrigues; Berneck, Bianca V M; da Silva, Helio R; Haddad, Célio F B; Zamudio, Kelly R; Mott, Tamí; Nali, Renato C; Prado, Cynthia P A
Abstract: Female fecundity is an important selective force leading to female-biased sexual size dimorphism (SSD) in frogs. Because anurans exhibit diverse reproductive modes, we investigated whether variation in SSD and fecundity are related with oviposition site. We asked whether arboreal breeding species show pronounced female-biased SSD and if, paradoxically, females have lower fecundity because of the costs of carrying oocytes and amplectant males. Conversely, we tested whether species that deposit eggs in concealed sites show less pronounced SSD, because females do not carry males and space limitation may reduce female size and fecundity. Our results showed that, in general, males were approximately 20% smaller than females. However, for species with hidden oviposition sites, males and females exhibited more similar body sizes and arboreal hylids showed more pronounced female-biased SSD. Overall, fecundity was higher in aquatic breeders, as expected, but in hylids, fecundity was smaller in arboreal breeders, which suggests that arboreality may impose restrictions on fecundity. By analysing SSD in a broader and more specific lineage (Hylidae), we found that reproductive microhabitat may also influence female size and fecundity, playing an important role in the evolution of SSD in frogs at different evolutionary scales.